The Sky Ride (Arena Photo Post Card Co.)
Two towers, each 628 feet high, the highest structures west of New York, standing 1,850 feet apart with observation rooms atop them. On the 200 foot level the rocket cars offer a beautiful and thrilling ride across the lagoon. These cars are double decked and travel on four cables, the span of which is the second longest in the world.